Membuat Rajutan Dari Benang Wol Sebagai Produk UMKM Pondok Tahfidz - Deliani, Susy; Zahara, Siti Fatimah; Muliatik, Sri; Harahap, Andi Syahputra; Siahaan, Hasnah (Jurnal Pengabdian Masyarakat Inovasi, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) sector based on handicrafts plays a strategic role in supporting household economies, including within religious educational institutions. This community service aims to empower students at Pondok Tahfidz Layar Dakwah through training in knitting crafts using wool yarn as an effort to create economic independence. The method used is Participatory Action Research (PAR), which includes observation stages, theoretical presentations, demonstrations of knitting techniques, and independent production practice. The program was conducted over two months (June-July) focusing on mastering basic techniques such as single crochet, double crochet, and slip stitch. The results of the service showed a significant increase in the students' skills, rising from 3.4% to 96.6% in their ability to produce marketable knitted bags. In addition to providing economic benefits through the formation of the boarding school's MSME unit, this knitting activity also serves as a means of mental relaxation (self-care) for students amidst their Al-Qur'an memorization routines. This program concludes that the integration of handicraft skills and entrepreneurship within the tahfidz boarding school environment is capable of creating a sustainable creative economic ecosystem.